An analysis of South African Revenue Service powers to request relevant material as it pertains to the so-called ‘lifestyle questionnaire’. - Mayezana, Mbuyiseli (Department of Finance and Tax, 2020)
This study focuses on the South African Revenue Service’s (SARS) powers to request “relevant material” as it pertains to the so called ‘lifestyle questionnaire”. It also deals with taxpayer’s rights in terms of the Tax Administration Act No. 28 of 2011 (TAA) and the Constitution of the Republic of South Africa, 1996 (the Constitution). Furthermore, the definition of “relevant material’ was discussed in order to establish whether or not a “lifestyle questionnaire” falls within the broad definition of “relevant material” as defined in the TAA and whether or not it infringes upon the taxpayer’s fundamental rights contained in the Bill of Rights. The taxpayer’s remedies were also examined. The South African Revenue Act No. 34 of 1997 (SARS Act) provides that SARS must ensure efficiency and effectiveness of collection of all revenue. SARS must perform this function in the most cost efficient manner and in accordance with the values and principles mentioned in section 195 of the Constitution. SARS administers various pieces of legislation including the (TAA). The TAA was promulgated on 4th July 2012, came into effect on 1 October 2012 and incorporated into once piece of legislation certain administrative sections generic to all tax Acts excluding the Customs and Excise Act. Both SARS and taxpayers must adhere to the Constitution of the Republic which is the supreme law of the country. Any law or conduct inconsistent with the Constitution is invalid. The Constitution consists of the Bill of Rights, a cornerstone of the South African democracy. SARS is an organ of state and therefore must respect, protect and promote the rights contained in the Bill of Rights. Since the introduction of the TAA, taxpayers feel that SARS’ powers have been enhanced. Section 46 of the TAA empowers SARS to request relevant material in various ways for the purpose of administration of a Tax Act, one of which could be by way of issuing a “lifestyle questionnaire” to taxpayers. A Lifestyle questionnaire requires details of the taxpayer’s assets and liabilities, income and expenses for the current and future tax years. Taxpayers often feel that this document is not specific but wide, because they are obliged to reveal everything to the SARS officials. This study reveals that the information requested though the “lifestyle questionnaire” is “in the opinion of SARS foreseeably relevant” for the administration of a tax Act. It therefore, falls within the definition of relevant material. Taxpayers may not without just cause refuse to complete and file the lifestyle questionnaire when requested to do so. It was further established that the Constitutional rights in the Bill of Rights are not absolute. Taxpayers who wish to challenge SARS’ decision to issue a lifestyle questionnaire need to be aware of their rights and the limitations thereof. In addition, this dissertation has revealed that a decision taken by SARS to issue a lifestyle questionnaire is an initial stage, the responses to which could trigger an investigation or audit and that the taxpayer’s Constitutional rights are not adversely affected by such a request. Therefore, taxpayers might encounter difficulty in successfully challenging SARS on judicial review by The High Court. The most suitable, cost effective and expeditious remedy that may be explored by any aggrieved taxpayer is that of the office of the Tax Ombudsman. The mandate of the Tax Ombud is to review and address any complaint by a taxpayer regarding a service or a procedural or administrative matter arising from the application of a tax Act